2017
DOI: 10.1183/13993003.01934-2016
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea and related comorbidities in incident idiopathic pulmonary fibrosis

Abstract: The objectives of this prospective study were: 1) to determine the prevalence and determinants of obstructive sleep apnoea (OSA) in patients with newly diagnosed idiopathic pulmonary fibrosis (IPF); 2) to determine whether OSA was associated with cardiovascular disease (CVD) as well as increased oxidative stress and levels of IPF biomarkers in the blood.A group of 45 patients with newly diagnosed IPF attended polysomnography. The prevalence of CVD and the severity of coronary artery calcification were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 36 publications
5
56
3
4
Order By: Relevance
“…In a recent prospective French study, moderate-to-severe OSA was frequently detected at the time of IPF diagnosis (62% of cases), while cardiovascular comorbidities, particularly ischaemic heart disease (IHD), were more frequently found in IPF patients with severe OSA than in IPF patients with no or mild-to-moderate OSA. The presence of moderate-to-severe coronary artery calcifications on HRCT was strongly associated with severe OSA [108]. Previous studies reported a higher prevalence of IHD in IPF patients than in matched COPD or emphysema patients, independently of common coronary artery risk factors [109][110][111][112][113].…”
Section: Sleep Apnoeamentioning
confidence: 81%
See 1 more Smart Citation
“…In a recent prospective French study, moderate-to-severe OSA was frequently detected at the time of IPF diagnosis (62% of cases), while cardiovascular comorbidities, particularly ischaemic heart disease (IHD), were more frequently found in IPF patients with severe OSA than in IPF patients with no or mild-to-moderate OSA. The presence of moderate-to-severe coronary artery calcifications on HRCT was strongly associated with severe OSA [108]. Previous studies reported a higher prevalence of IHD in IPF patients than in matched COPD or emphysema patients, independently of common coronary artery risk factors [109][110][111][112][113].…”
Section: Sleep Apnoeamentioning
confidence: 81%
“…Nocturnal hypoxaemia is closely related to increments in right ventricular systolic pressure values associated with increased pulmonary hypertension [114,115]. To detect occult OSA, nocturnal polysomnography should be performed at the time of IPF diagnosis, especially when moderate-to-severe coronary artery calcifications are seen on HRCT images [108]. The use of continuous positive airway pressure results in significant improvements in activities of daily living, quality of sleep, QoL and survival [100].…”
Section: Sleep Apnoeamentioning
confidence: 99%
“…Preliminary studies suggest that OSA may be an underappreciated comorbid condition in those with IPF. Three investigations have shown OSA to be present in 58–88% of patients with IPF, with up to 68% having moderate-to-severe OSA based on an apnea–hypopnea index ≥15 events/hour ( 52 54 ). In addition, severe sleep apnea was recently shown to be strongly associated with ischemic heart disease in patients with IPF ( 54 ).…”
Section: Pulmonary Comorbiditiesmentioning
confidence: 99%
“…The clinical picture of IPF also involves comorbidities. Conditions which are more frequent in IPF patients than in the general population include gastroesophageal reflux disease (GERD) [39][40][41], lung cancer [42,43], emphysema [42,44], pulmonary hypertension [38,45,46] and obstructive sleep apnoea [47]. Other common diseases characteristic of this age group include hypertension, ischaemic heart disease, cardiac arrhythmias, stroke, other forms of arterial atherosclerosis, depression, venous thromboembolism and diabetes [48,49].…”
Section: Clinical Picturementioning
confidence: 99%